Peningkatan Kapasitas Peternak Rakyat Pada Pengelolaan Kesehatan Ternak Sapi Potong di Desa Tampelas, Kabupaten Katingan - Ria Anjalani; Paulini; Sosilawaty; Nyahu Rumbang; Trisna Anggreini; Erina Riak Asie; Satrio Wibowo (Jurnal Pengabdian Kampus, 2023)
Tampelas Village is located in Kamipang District, Katingan Regency, Central Kalimantan. Most of the residents have their main livelihood as traditional fishermen. Beef cattle farming is also carried out in Tampelas Village by several members of the community in a traditional way. Farmers lack knowledge regarding the management of the health of their livestock. The capacity building training in livestock health management aims to provide farmers with knowledge, insight, and skills related to the management of the health of beef cattle. The training consists of delivering material, hands-on practice by farmers, and discussions. The material presented included prevention, identification of livestock conditions and diseases, introduction of types of medicines, and handling of sick livestock. The activity was attended by farmers, village officials and staff from the relevant Katingan Regency Goverment. Training activities to increase the capacity of livestock health management in Tampelas Village went well. Beef cattle farmers in Tampelas Village are enthusiastic and welcome the livestock health management training activities. Their insight, knowledge and skills related to livestock health management have increased.